Hyponatremia presenting with hourly fluctuating urine osmolality - Raku Son; Masahiko Nagahama; Fumiaki Tanemoto; Yugo Ito; Fumika Taki; Ryosuke Tsugitomi; Masaaki Nakayama (Endocrinology, Diabetes & Metabolism Case Reports, 2020)
The etiology of hyponatremia is assessed based on urine osmolality and sodium. We herein describe a 35-year-old Asian man with pulmonary tuberculosis and perforated duodenal ulcer who presented with hyponatremia with hourly fluctuating urine osmolality ranging from 100 to 600 mosmol/kg, which resembled urine osmolality observed in typical polydipsia and SIADH simultaneously. Further review revealed correlation of body temperature and urine osmolality. Since fever is a known non-osmotic stimulus of ADH secretion, we theorized that hyponatremia in this patient was due to transient ADH secretion due to fever. In our case, empiric exogenous glucocorticoid suppressed transient non-osmotic ADH secretion and urine osmolality showed highly variable concentrations. Transient ADH secretion-related hyponatremia may be underrecognized due to occasional empiric glucocorticoid administration in patients with critical illnesses. Repeatedly monitoring of urine chemistries and interpretation of urine chemistries with careful review of non-osmotic stimuli of ADH including fever is crucial in recognition of this etiology.